The Relationship Between Socio-Cultural, Accessibility and Motivation of Mother with Complete Basic Immunization Status - Frastica Rahmadhani, Youris; Parellangi, Andi; Abdul Syukur, Nursari (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The Ujoh Bilang Health Center, located in Mahakam Ulu Regency, is known to have complete basic immunization coverage from January to December 2022 for 12-month-old children of 143 children (59%) with a target of 241 children. This shows that the complete basic immunization coverage is still below the Mahakam Ulu Regency target of 93.6% and the national target of 93%. Objective: The aim is to know the relationship socio-cultural, accessibility and motivation of mothers with complete basic immunization status in the working area of the Ujoh Bilang Health Center. Methods: This type of research is analytic observation using a cross sectional design. Data analysis using Chi-Square. Results and Discussion: Characteristics of respondents aged between 20-35 years (95.8%), multipara parity (66.2%), high school graduate education (57.7%), work as an IRT (46.5%), socio-cultural good (53.5%), less supportive accessibility (54.9%), good motivation (52.1%), and complete basic immunization status (50.7%). There is a socio-cultural relationship (p-value: 0.044), accessibility (p value: 0.012), mother's motivation (p value: 0.024) with complete basic immunization status in the working area of the Ujoh Bilang Health Center. Conclusion: Socio-cultural, accessibility and mother's motivation are related to complete basic immunization status